Educate and train healthcare professionals and healthcare profession students and make aware public about reporting adverse drug reactions (ADRs) - Piryani, Rano Mal; Piryani, Suneel (Journal of Liaquat University of Medical & Health Sciences, 2022)
Educate and train healthcare professionals and healthcare profession students and make aware public about reporting adverse drug reactions (ADRs)